“Ah non, je ne parle pas anglais moi. Je suis française !” Une contribution à la typologie des pragmatèmes - de Oliveira, Ruth (Neophilologica, 2020)
This work presents and discusses the development of the hypothesis according to which clitic doubling (pronominal reduplication), as seen in the sentence “Je ne parle pas anglais moi. / I do not speak English [me]”, has the fundamental structural and pragmatic parameters of the pragmatem (R. D e O l i v e i r a, 2018). Structural, because it is a compositional construction but selected as a whole by the speaker to respond to a communication goal associated with a precise utterance situation (G. F l é c h o n et al., 2012); pragmatic, since this device is a means of acting on the interlocutive context, allowing the accomplishment of a certain number of specific acts (I. M e l’č u k, 2013). In this sense, we argue that, like the pragmatem, the devise called French clitic doubling simultaneously has the following three characteristics, it is (i) fixed, (ii) compositional, and (iii) associated with a specific utterance situation.